Association of the ACE, GSTM1, IL-6, NOS3, and CYP1A1 polymorphisms with susceptibility of mycoplasma pneumoniae pneumonia in Chinese children. Issue 15 (April 2017) - Zhao, Jie; Zhang, Wen; Shen, Li; Yang, Xiaomeng; Liu, Yi; Gai, Zhongtao
Abstract : Abstract: Mycoplasma pneumoniae is a common cause of community-acquired pneumonia (CAP) and the clinical presentation of mycoplasma pneumoniae pneumonia (MPP) varies widely. Genetic variability affecting the host response may also influence the susceptibility to MPP. Several studies have investigated the association between single nucleotide polymorphism (SNP) of some genes and the risks of CAP; however, the results were inconsistent. Here, we investigated the association of 5 functional genes and the risks of MPP, including ACE (rs4340), GSTM1 (Ins/del), IL-6 (rs1800795), NOS3 (rs1799983), and CYP1A1 (rs2606345) in a total of 715 subjects (415 cases, 300 controls) by using tetra-primer allele-specific polymerase chain reaction (PCR) and Sanger sequencing. The gene–gene interactions were analyzed using the Multifactor Dimensionality Reduction and cumulative genetic risk score approaches. Our results showed that 3 SNPs of ACE rs4340, IL-6 rs1800795, and NOS3 rs1799983 were significantly associated with the risks of MPP, while no differences were observed in genotype frequencies of GSTM1 (Ins/del) and CYP1A1 rs2606345 between both groups. The combinations of ACE rs4340D/NOS3 rs1799983T/CYP1A1 rs2606345G and ACE rs4340D/NOS3 rs1799983T contribute to the genetic susceptibility of MPP in Chinese children.